An Old Age-Distinction Reported by Observing New Technologies - Raglianti, Felipe (Universidad de Chile. Instituto de la Comunicación e Imagen, 2010)
New technologies have become an Old age indicator, through the relationship between age and be technology's expertise. The information society builds, therefore, a series of semantic narratives on old age. Such distinctions are in current construction, so that the relationship between age and technology, although observable, is still controversial.